PERAN RADIO SWASTA BAGI PERKEMBANGAN KREASI MUSIK INDIE DI KOTA CIREBON (Studi Deskriptif Kualitatif pada Program Hot Indie 12 di Radio Nuansa Cirebon) - Liling Kuning; H. Mukarto Siswoyo; Welly Wihayati (Universitas Swadaya Gunung Djati, 2013)
Radio is one of the media of mass communication. The existence and development of radio inIndonesia has been very rapid. Research Objectives: 1. To find out the program Hot Indie 12 ingrowing the audience; 2. To find out the program Hot Indie 12 in attracting listeners; 3. To findout the program Hot Indie satisfy listeners 12 4. To determine the program's decision to develop12 Hot Indie indie music creation; 5. To determine the implementation of 12 in developing HotIndie indie music creation. The method of research used qualitative descriptive method. Theresults of the study were: 1. Expertise and skills in bringing the program broadcast announcercan attract attention (attention) listeners. 2. Concept and Promotion Programs can be interesting(interest) listeners to participate in the program Hot Indie 12. 3. Segmentation and Target is acommunity program or indie band Cirebon City 4. Profile program 12 Hot Indie Radio Nuancebegins with an idea, the idea and concept that is based on segmentation and target programs thathave been established by the Radio Nuance. 5. Activity (action) is the end of a series ofprocesses and presentation of broadcast programs in terms of realization and selection process 12indie band Hot Indie Program 12 so as to develop creative indie music in the city of Cirebon.Radio merupakan salah satu media komunikasi massa. Keberadaan dan perkembangan radio diIndonesia sudah sangat pesat. Tujuan Penelitian : 1. Untuk mengetahui program Hot Indie 12dalam menumbuhkan perhatian pendengar; 2. Untuk mengetahui program Hot Indie 12 dalammenarik minat pendengar; 3. Untuk mengetahui program Hot Indie 12 memenuhi keinginanpendengar; 4. Untuk mengetahui keputusan program Hot Indie 12 dalam mengembangkan kreasimusik indie; 5. Untuk mengetahui pelaksanaan Program Hot Indie 12 dalam mengembangkankreasi musik indie. Metode penelitian yang digunakan metode deskriptif kualitatif. Hasil daripenelitian ; 1. Keahlian dan keterampilan penyiar dalam membawakan siaran program dapatmenarik perhatian (attention) pendengar. 2. Konsep dan Promosi Program dapat menarik minat(interest) pendengar untuk berpartisipasi dalam program Hot Indie 12. 3. Segmentasi dan Targetprogram adalah komunitas atau band indie Kota Cirebon 4. Profil program Hot Indie 12 RadioNuansa bermula dari sebuah ide, gagasan dan konsep yang disusun berdasarkan segmentasi dantarget program yang telah ditetapkan oleh Radio Nuansa. 5. Kegiatan (action) merupakan prosesakhir dari serangkaian proses dan penyajian siaran program yang ditinjau dari realisasi danproses seleksi 12 band indie dalam Program Hot Indie 12 sehingga dapat mengembangkan kreasimusik indie di Kota Cirebon.Key Words : Peran, Radio, Kreasi